2011
DOI: 10.1177/0192623310396904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carcinogenic Potential of Diuron in a Rat Mammary Two-Stage Carcinogenesis Model

Abstract: This study aimed to evaluate the carcinogenic potential of the herbicide Diuron in a two-stage rat medium-term mammary carcinogenesis model initiated by 7,12-dimethylbenz(a)anthracene (DMBA). Female seven-week-old Sprague-Dawley (SD) rats were allocated to six groups: groups G1 to G4 received intragastrically (i.g.) a single 50 mg/kg dose of DMBA; groups G5 and G6 received single administration of canola oil (vehicle of DMBA). Groups G1 and G5 received a basal diet, and groups G2, G3, G4, and G6 were fed the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This finding is consistent with the findings of Grassi et al (2011). They found, however, that the potentiation after high frequency stimulation was markedly reduced in the presence of letrozole in males compared to that induced under control conditions.…”
Section: Sex-specific Paracrine Effects Of Sn On Hippocampal Synapticsupporting
confidence: 92%
“…This finding is consistent with the findings of Grassi et al (2011). They found, however, that the potentiation after high frequency stimulation was markedly reduced in the presence of letrozole in males compared to that induced under control conditions.…”
Section: Sex-specific Paracrine Effects Of Sn On Hippocampal Synapticsupporting
confidence: 92%
“…Proliferating cell nuclear antigen (PCNA) is a 36 kDa molecule that acts as a DNA polymerase co-factor during chromosome replication and is easily detected during S-phase of the cell cycle [29]. Therefore, PCNA is widely used as a reliable cell proliferation biomarker in experimental models of chemical carcinogenesis, including models of rat mammary carcinogenesis [24,29,30]. In the present study, the reduced PCNA LI% observed in TAM-treated rats can be explained by the ability of TAM to inhibit estrogen receptor (ER)-dependent cell proliferation in mammary tumors [31].…”
Section: Discussionmentioning
confidence: 99%
“…1) and mammary glands removed and fixed for 24 hr in 10% phosphate‐buffered formalin. Samples of organs/tissues were processed in order to provide 5 µm‐thick paraffin sections for histology (hematoxylin–eosin]) and immunohistochemical analysis for proliferating cell nuclear antigen (PCNA), cleaved caspase‐3 and estrogen‐receptor‐alpha (ER‐α) (Grassi et al, 2011).…”
Section: Methodsmentioning
confidence: 99%